2020
DOI: 10.1111/wrr.12811
|View full text |Cite
|
Sign up to set email alerts
|

Liposome‐encapsulated statins reduce hypertrophic scarring through topical application

Abstract: Hypertrophic scar is an important clinical problem with limited therapeutic options. Aside from their roles as 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase inhibitors, statins have also been demonstrated to decrease scarring by reducing connective tissue growth factor (CTGF) expression. However, poor penetrative ability limits their utility as topical treatments for hypertrophic scar. Here, we aim to develop novel statin formulations using liposomes to enhance dermal penetrative ability and to evaluate thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In an animal model, Ko and colleagues have suggested that low dosages of statins (40 mictoM) were associated with significant reductions in the scar elevation index (SEI) compared to an untreated control group, through a mechanism mediated by the reduction of connective tissue growth factor (CTGF) 28 . Recently, Xia et al found that simvastatin seems to inhibit the gene and the protein expression of CTGF and that liposome‐encapsulated statins might reduce hypertrophic scarring though topical application 29 . The same research team then assessed the effectiveness of statin on the wound healing process in an animal model in which the using the SEI, a ratio of cross‐sectional scar area to the area of tissue was assessed 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, Ko and colleagues have suggested that low dosages of statins (40 mictoM) were associated with significant reductions in the scar elevation index (SEI) compared to an untreated control group, through a mechanism mediated by the reduction of connective tissue growth factor (CTGF) 28 . Recently, Xia et al found that simvastatin seems to inhibit the gene and the protein expression of CTGF and that liposome‐encapsulated statins might reduce hypertrophic scarring though topical application 29 . The same research team then assessed the effectiveness of statin on the wound healing process in an animal model in which the using the SEI, a ratio of cross‐sectional scar area to the area of tissue was assessed 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our laboratory has demonstrated that application of statins is sufficient to reduce hypertrophic scarring in preclinical rabbit ear models of excisional wounding. We demonstrated amelioration of excisional wound‐induced hypertrophy by application of statins through intradermal injection, 5,6 topical application within emulsifications delivered in transcutol/capmul, 6 and topical application in liposomal formulations 7 . In order to optimize ease‐of‐use clinically in a cost‐effective and traditional drug delivery vehicle, we formulated a statin‐containing cream formulation for topical application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, statins demonstrate a promising therapeutic potential in the field of bone tissue engineering and bone regeneration due to their ability to promote the expression of bone morphogenetic proteins (BMPs) and vascular endothelial growth factor (VEGF) [ 8 ]. Statins have been shown to decrease hypertrophic scarring by reducing the expression of connective tissue growth factor (CTGF) and type I/III collagen content [ 9 ]. There is also evidence for the therapeutic potential of statins for the treatment of chronic liver disease and cirrhosis by exerting anti-fibrotic and vasoprotective effects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve their therapeutic benefits, numerous nanotechnology-based drug delivery systems were developed [ 25 , 26 , 27 , 28 ]. The enhancement of statins’ pharmacological parameters can be achieved by using nano-sized systems and functional nanomaterials, including nanoparticles [ 25 , 27 , 29 ], nanoliposomes [ 9 ], nanocrystals [ 30 ] as well as self-nanoemulsifying systems [ 31 , 32 ]. Due to the wide spectrum of potential benefits of statins, research efforts should also focus on the identification of new targets and deeper understanding of the underlying mechanisms of statin pleiotropy.…”
Section: Introductionmentioning
confidence: 99%